Cybercrime, Differential Association, and Self-Control: Knowledge Transmission Through Online Social Learning - Dearden, Thomas E. (American journal of criminal justice, 2021)
In an increasingly digital world, our social interactions are increasingly moving online. Differential association and social learning theories suggest that we learn both moral definitions and the how-to of crime from those we associate with. In this paper we examine whether online or offline social learning leads to more self-disclosed forms of cyber-offending. Using a national online sample of 1,109 participants, we find both online and offline social learning are important correlates to cyber-offending. In addition, we predict that lower self-control will interact with social learning to further increase the likelihood of cyber-offending. Overall, we find that both social learning and self-control, individually and as an interaction, have a large effect-size in predicting cyber-offending.